2021
DOI: 10.3390/polym13224040
|View full text |Cite
|
Sign up to set email alerts
|

A Degradable Inverse Vulcanized Copolymer as a Coating Material for Urea Produced under Optimized Conditions

Abstract: Global enhancement of crop yield is achieved using chemical fertilizers; however, agro-economy is affected due to poor nutrient uptake efficacy (NUE), which also causes environmental pollution. Encapsulating urea granules with hydrophobic material can be one solution. Additionally, the inverse vulcanized copolymer obtained from vegetable oils are a new class of green sulfur-enriched polymer with good biodegradation and better sulfur oxidation potential, but they possess unreacted sulfur, which leads to void ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This method involves the usage of color reagent, which was prepared by mixing the 25 ml of DAM solution (prepared by dissolving 2.5 g of diacetyl monoxime in 100 ml of distilled water), 15 ml of TSC solution (prepared by dissolving 0.25 g of thiosemicarbazide in 100 ml of distilled water) and 460 ml of acid reagent (prepared by mixing 10 ml of sulfuric acid, 240 ml of distilled water and 250 ml of phosphoric acid). 20,21,28 2 g of coated urea was placed in a conical flask containing 200 ml of distilled water. To estimate the amount of the nitrogen released in distilled water from coated urea, after every 24 h 2.5 ml of the aliquot was taken and mixed with 7.5 ml of the color reagent and heated to a temperature of 85 °C for 30 min in a water bath followed by cooling at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method involves the usage of color reagent, which was prepared by mixing the 25 ml of DAM solution (prepared by dissolving 2.5 g of diacetyl monoxime in 100 ml of distilled water), 15 ml of TSC solution (prepared by dissolving 0.25 g of thiosemicarbazide in 100 ml of distilled water) and 460 ml of acid reagent (prepared by mixing 10 ml of sulfuric acid, 240 ml of distilled water and 250 ml of phosphoric acid). 20,21,28 2 g of coated urea was placed in a conical flask containing 200 ml of distilled water. To estimate the amount of the nitrogen released in distilled water from coated urea, after every 24 h 2.5 ml of the aliquot was taken and mixed with 7.5 ml of the color reagent and heated to a temperature of 85 °C for 30 min in a water bath followed by cooling at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained red color solutions were then analysed using Shimadzu UV-1800 UV-Vis spectrophotometer at 526 nm wavelength. 13,20,21…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Various types of coating materials have been used to produce urea based CRF such as sulphur, synthetic polymers, or biopolymers. [9][10][11][12] Suherman et al 13 reported that sulphur-coated urea exhibited a delayed urea release rate with 0.038 to 0.047 g s −1 as compared to uncoated urea release rate of 0.060 g s −1 . In another study, nutrient release in soil from uncoated urea was 100% while sulphur-coated urea showed ∼32% release aer 7 days of application.…”
Section: Introductionmentioning
confidence: 99%